(untitled) (CIPEEX, 2025)
This paper examines the Superior Court of Justice’s settled understanding that irregularities occurring during the preliminary investigation—an informational, non-essential stage—do not automatically nullify the criminal action. The aim is to set practical criteria for when defects in the police inquiry may taint the prosecution, under the pas de nullité sans grief principle, which requires proof of actual prejudice to the defendant. Methodologically, it conducts a case-law review emphasizing HC 460.684/SC and HC 597.051/SP, which, respectively, illustrate the need for a prejudice nexus and the sufficiency of independent evidence to support the charge. The findings indicate that investigative defects affect the criminal case only when they concretely impair the right to defense; where autonomous proof exists, proceedings may continue, thereby avoiding the invalidation of prosecutions due to minor investigative errors. The conclusion is that a rigorous prejudice assessment enhances legal certainty and preserves procedural integrity, since defects arising during the investigation generally do not impact the criminal action absent demonstrable and insurmountable harm.